The Age of god-kings : 3000-1500 BC - Time-Life Books (Amsterdam : Time-Life Books, 1991)
1. World history--3000-1500 BC
Includes bibliographical references.
Bibliography: p. 168-169.
Basic Ed. Students
Keywords: History, Ancient